Which Households Respond to Electricity Peak Pricing Amid High Levels of Electrification? - Cloé Garnache; Øystein Hernæs; Anders Gravir Imenes (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine heterogeneity in Norwegian households' price responses to critical peak pricing (CPP) on electricity consumption, using a large-scale randomized controlled trial (RCT), high-frequency electricity data, and default enrollment. Increasing the grid transmission charge by 4,067% (corresponding to an increase in the electricity price by 1,242%) leads to a 12.5% reduction in consumption, and virtually eliminates the consumption “peak”. In contrast to prior studies from less electrified countries, the effect is broad-based, and similar across income groups. These findings provide a unique lens into the effectiveness of demand-based policies, and their impact across household groups, in a more electrified future.
Keywords: C93; D12; L94; Q41; 330; critical peak pricing; grid transmission charge; peak demand; household heterogeneity; RCT; default enrollment; electrification